Location of Signs and Symptoms of Gout Arthritis Patients - Magda Fiske Rumambi; Rosiana Sitio; Sari Putri Rohani Sidauruk; Stephany Angeline Kristanti; Ballsy Cicilia Albertina Pangkey (Holistic Nursing and Health Science, 2025)
Gouty arthritis is a joint disorder that is on the rise among adults worldwide experiencing pain and swelling. Gouty arthritis often causes significant pain and swelling that can limit physical activity due to joint damage. Recently, lack of detailed information regarding the location pain and swelling. Therefore, this study aimed to identify characteristics (age, gender, BMI, and alcohol consumption), pain location and swelling location in patients with gouty arthritis at a private hospital in Western Indonesia. This study used quantitative methods with a retrospective documentation design. The sampling technique was total sampling, involving 47 medical records from one of the private hospitals in Western Indonesia. Instrument, data analysis The results of the study showed that pain most frequently occurred in the infrapatellar bursa (34%), while swelling was not found in 34% of patients with gout arthritis. The instrument used was a form sheet consisting of demographic data and information regarding location of pain and swelling. The data was analyzed using univariate analysis. Results show that the most pain and swelling were found in the infrapatellar bursa. Further research is recommended to explore effective interventions for managing these symptoms. The high incidence of gouty arthritis in individuals aged 55–65 years highlights the importance of prioritizing screening and early detection efforts for this age group. Given the high frequency of pain and swelling complaints among patients, further research on appropriate management strategies is essential for individuals with gouty arthritis.